Diplomasi Israel dalam Menentang Upaya Palestina Menjadi Anggota Penuh PBB - Sari Hastuti (Jurnal Paradigma, 2013)
Palestinians submitted a proposal to become a full member of the United Nations in 2011 but did not receive enough support from the UN Security Council. Palestinians again proposed to increase membership status with the United Nations General Assembly in 2012. Israel saw the Palestinian as an attempt unilateral adverse political position Israel. This study aims to know the diplomacy Israel in opposing Palestinian efforts to become a full member of United Nations through bilateral and multilateral diplomacy. The results showed that Israel bilateral diplomacy has failed. The results showed that Israel through bilateral diplomacy has failed. Multilateral diplomacy has also failed to prevent an increase in Palestinian UM membership status. On 29 November 2012, the UN General Assembly decided to increase the status of the Palestinian to non-member observer state in the United nations. Palestinians was supported 138 countries, 41 countries abstained, and only 9 states that the Palestinians refused to increase membership status